The splicing fate of plant SPO11 genes - Sprink, Thorben; Hartung, Frank (Frontiers in Plant Science, 2014)
Towards the global understanding of plant meiosis, it seems to be essential to decipher why all as yet sequenced plants need or at least encode for two different meiotic SPO11 genes. This is in contrast to mammals and fungi, where only one SPO11 is present. Both SPO11 in plants are essential for the initiation of double strand breaks (DSBs) during the meiotic prophase. In nearly all eukaryotic organisms DSB induction by SPO11 leads to meiotic DSB repair, thereby ensuring the formation of a necessary number of crossovers (CO) as physical connections between the allelic chromosomes. We aim to investigate the specific functions and evolution of both SPO11 genes in land plants. Therefore, we identified and cloned the respective orthologous genes from Brassica rapa, Carica papaya, Oryza sativa and Physcomitrella patens. In parallel we determined the full length cDNA sequences of SPO11-1 and -2 from all of these plants by RT-PCR. During these experiments we observed that the analyzed plants exhibit a pattern of aberrant splicing products of both SPO11 mRNAs. Such an aberrant splicing has previously been described for Arabidopsis and therefore seems to be conserved throughout evolution. Most of the splicing forms of SPO11-1 and -2 seem to be non functional as they either showed intron retention or shortened exons accompanied by a frameshift leading to premature termination codons (PTCs) in most cases. Nevertheless, we could detect one putative functional alternatively spliced mRNA for SPO11-1 and -2 each, indicating that splicing of SPO11 does not depend only on the gene sequence but also on the plant species and that it might play a regulatory role.